Connecting Children to Nature - SHEFALI (THE PRIMARY TEACHER, 2014)
Teaching children about the environment is vital for the future of children and society. In an increasingly urban society adults need to create opportunities to help young children connect with environment and learn about the nature. There are many positive benefits when nature learning becomes a part of the child’s life. The children who have more enriching experiences in the environment are more likely to become adults who are better informed; they develop a better understanding towards the creatures i.e., they build a sense of care and responsibility towards earth.